Change Management: Why change fails? Why Change Failed in Gokul Group of Restaurants. - Mohan, Gopal (2013)
The focus of this research is to develop a deeper understanding of change management to understand why change fails in organizations and how organizations can successfully carry out change. Data has been gathered from the change efforts at Gokul Group of Restaurants using interviews aimed at finding out why change failed in GGR. A case study has also been used to provide the reference to the context of change efforts in GGR. Findings revealed that reasons for failure of change efforts in GGR can be tracked back to the literature discussed. Subsequently a phase-by-phase implementation plan has also been recommended for the implementation of future changes in GGR.